Framing Entrepreneurial Ideas for Sustainability: How Do Purpose‐Driven Startups Include the Sustainable Development Goals in Their Pitches? - Saari, Ulla A.; Aagaard, Annabeth; Achtenhagen, Leona; Mäkinen, Saku J. (Wiley, 2025)
This paper investigates how entrepreneurs frame the sustainability of their business ventures when pitching their business prospects and sustainability approaches to investors. Drawing on framing theory, this research explores the classification and application of sustainability-related frames employed in business pitches. A qualitative multiple case study methodology is applied to collect and analyze data from startup pitches presented at the startup event Slush, which is held annually in Finland. The sample consists of active startups and those that did not survive following the pitching event. The Need-Approach-Benefit-Competition (NABC) pitching model and the UN's Sustainable Development Goals serve as frameworks for systematically analyzing the content of the verbal pitch presentations. We disentangle how entrepreneurs formulate business ideas within frames related to sustainability themes on the micro, meso, and macro levels using cognitive, strategic, technological, and institutional frames. The resulting model distinguishes between different combinations of sustainability framing elements applied in startup pitches.